پاکستان میں مذہبی ہم آہنگی کی ضرورت و اہمیت قرآن کی روشنی میں:تحقیقی و تجزیاتی مطالعہ: Need and importance of religious harmony in Pakistan in the light of Quran: Exploratory and Analytical Studies - Jahangir Khan; Muhammad Farhan Ur Rehman (Corresponding Author); Muhammad Ajmal (International Research Journal of Arabic and Islamic Studies, 2023)
Allah Almighty has established humanity on a foundation of universality. From Hazrat Adam (peace be upon him) to our beloved Prophet Hazrat Mohammad (peace be upon him), all Prophets (peace be upon them) taught unity and brotherhood to their respective nations. As the human population grew, the need for mutual relations became crucial. Consequently, with this closeness, separation, comparisons, and opposing viewpoints also emerged. Over time, hatred, hypocrisy, and other social vices spread widely. Islamic history serves as a model where minorities were given opportunities to participate in political, educational, social, and collective affairs. In societies where tyranny, intolerance, injustice, religious extremism, terrorism, and human rights violations were prevalent, the Islamic ideal of forbearance replaced these vices. Our Prophet Hazrat Mohammad (SAWW) taught that all humanity is equal, with no differences among people. Today, it is essential to foster modesty, harmony, peacefulness, and affection among the diverse religious communities of Pakistani society. For this critical cause, all religious scholars and their followers must actively contribute. By doing so, the barriers of narrow-mindedness and religious hatred can be dismantled. It is crucial for Islamic scholars in Pakistan to promote religious tolerance and help create a harmonious society.